Evaluation of eco-friendly management of stem rot and root rot diseases of Olitorius jute (Corchorus olitorius L.) - P.S. NATH, SRABANI DEBNATH*, S. DAS, S. JENA and (Indian Phytopathology, 2016)
The soil borne disease, stem rot and root rot caused by the fungus Macrophomina phaseolina is the most devastating disease of Olitorius Jute. Because of it’s soil borne nature, it is very much difficult to manage. The pooled analysis of the result revealed that disease incidence of both stem rot and root rot was found lowest with the application of FYM @ 5t/ha + seed treatment with Azotobactor and PSB each @ 5g/kg of seed + T. viride soil application @ 2g/kg at 21 DAS + Fluorescent Pseudomonas spray @0.2% at 45 DAS + neem oil @0.03% and Bt@1g/litre of water at 40 and 65 DAS (T5) followed by use of 50% NPK+ seed treatment with Azotobactor and PSB each @ 5g/kg of seed + Trichoderma viride soil application @ 2g/kg at 21 DAS + Fluorescent Pseudomonas spray @0.2% at 45 DAS + neem oil @ 0.03% and Bt @1g/litre of water at 40 and 65 DAS (T3) without significant difference . Significantly higher fibre yield (29.35q/ha) of jute was obtained in T5 followed by T3 (23.78q/ha). Like fibre yield, B:C ratio was also recorded highest in T5. Hence, based on disease infestation, fibre yield and B:C ratio application of - FYM @5t/ha + seed treatment with Azotobactor &PSB each @5g/kg of seed + T. viride soil application @2g/kg at 21 DAS +Fluorescent Pseudomonas spray @0.2% at 45 DAS + neem oil @0.03% and Bt@1g/litre of water at 40 and 65 DAS was found best management for stem rot and root rot disease of Jute.